Effect of Seating Location on Undergraduates’ Performance Based on Classroom Size and Quadrant Surveying: A Chinese empirical analysis - Siyu Yu; Xiaoyue Zhang; Rong Tao; Wanyu Huang; Jiangsheng Chen; Xieyu Xiao (SAGE Open, 2025)
This study explores the relationship between seating quadrants and student performance, including the role of classroom type in the quadrant effect. Data collected from 131 classes taught at 17 colleges of Northwest A&F University in China were analyzed using the ordinary least squares method. The results revealed that where a student sat in a classroom always had a significant effect on their performance. Classroom type also played an important role in students’ academic performance, specifically, the longer the depth of the classroom, the more obvious the quadrant effect. Additionally, different classroom utilization schemes resulted in different student densities in the classrooms, further affecting students’ academic performance. The higher the student density, the better the academic performance. We thus propose that the classroom utilization schemes should be in line with the matching relationship between student density and the classroom and that students be taught in small classrooms as much as possible.